Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

I’m a little unsure how to simplify the following expression: $$ x\left(\frac{y^{3}}{x^{4}}\right)^{1/4} $$

According to the answer, this should get you $\;\; x y^{3/4} x^{-1} = y^{3/4} $.

My intuition tells me that when we bring up $ \,x^{4} \,$ from the denominator, we get $ \,x^{-4}\, $ (with a negative power). In general, I’m unsure how $ x $ on the outside should multiply with what is inside the brackets. (Following BEDMAS, brackets should go first, right?)

share|improve this question
    
Please use LaTeX formatting next time. –  nbubis Feb 26 '13 at 19:16
    
I would also suggest using \frac instead of /. –  sonystarmap Feb 26 '13 at 19:16

2 Answers 2

up vote 1 down vote accepted

You have $$ x\Bigl(\frac{y^3}{x^4}\Bigr)^{\frac{1}{4}}$$ You can leave out the braces, if you apply the exponent $\frac14$ to each, nominator and denominator. Thus $$ x\Bigl(\frac{y^3}{x^4}\Bigr)^{\frac{1}{4}}=x\frac{y^\frac{3}{4}}{x^1}$$ Now as $\frac{1}{x} = x^{-1}$ you get $$ x\Bigl(\frac{y^3}{x^4}\Bigr)^{\frac{1}{4}}=x{y^\frac{3}{4}}{x^{-1}}=x^{1-1} y^\frac34= y^\frac34$$

share|improve this answer
    
x^1/4*X^4 should be x(^1)? if I'm reading that right ? if so this solution is more elegant. –  peter_gent Feb 26 '13 at 19:37
    
No $x^\frac14 \cdot x^4 = x^{\frac14+4}=x^\frac{17}{4}$. But $\bigl(x^\frac14 \bigr)^{4} = x^{\frac14\cdot 4} = x^1 = x$. –  sonystarmap Feb 26 '13 at 19:48
    
good solution anyway. thanks, this is much more straightforward. –  peter_gent Feb 26 '13 at 19:58
1  
I wouldn't say, that my solution is better than the one of @amWhy. Note, that he is more detailed and really takes his time with his comments. –  sonystarmap Feb 26 '13 at 20:01

$$ \begin{align} x\left(\frac{y^3}{x^4}\right)^{1/4} \\ \\ & = x(y^3x^{-4})^{1/4} \\ \\ & = xy^{3(1/4)}x^{-4(1/4)} \\ \\ & = xy^{3/4}x^{-1} \\ \\ & = xx^{-1}y^{3/4} \\ \\ & = \frac xx (y^{3/4}) \\ \\ & = y^{3/4} \\ \\ \end{align} $$

share|improve this answer
    
so the y^3 multiplies with ^-4 to give you 3/4? What about the remaining X on the outside or the ^1\4 power ? –  peter_gent Feb 26 '13 at 19:21
    
No, the $y^3$ becomes $y^{3(1/4)} = y^{3/4}$ and $x^{-4}$ becomes $x^{-4(1/4)} = x^{-1}$ I edited to make this clearer to you. –  amWhy Feb 26 '13 at 19:24
    
Does that make sense now? You distribute the exponent $1/4$ over $y^3x^{-4}$ –  amWhy Feb 26 '13 at 19:27
    
can anyone explain why you can gather powers like in step 2? Is it because of commutivity ? (sorry laggy internet on this one) –  peter_gent Feb 26 '13 at 19:31
    
Do you mean placing x next to $x^{−1}$? Yes, multiplication is commutative, so you can rearrange/commute factors. ...Perhaps you mean why $(y^3x^{-4})^{1/4} = y^{3/4}x^{-4/4} = y^{3/4}x^{-1}\,$? Because one of the laws of exponents is $(ab)^c = a^cb^c$. So $(a^db^e)^c = a^{c \cdot d}b^{c\cdot e}$ –  amWhy Feb 26 '13 at 19:38

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.